A MULTIWAVELENGTH STUDY OF CYGNUS X-1: THE FIRST MID-INFRARED SPECTROSCOPIC DETECTION OF COMPACT JETS - Rahoui, Farid; Lee, Julia C.; Heinz, Sebastian; Hines, Dean C.; Pottschmidt, Katja; Wilms, Jörn; Grinberg, Victoria (Astrophysical Journal, 2011)
We report on a Spitzer/InfraRed Spectrograph (mid-infrared), RXTE/PCA+HEXTE (X-ray), and Ryle (radio) simultaneous multiwavelength study of the microquasar Cygnus X-1, which aimed at an investigation of the origin of its mid-infrared emission. Compact jets were present in two out of three observations, and we show that they strongly contribute to the mid-infrared continuum. During the first observation, we detect the spectral break-where the transition from the optically thick to the optically thin regime takes place-at about 2.9x10(13) Hz. We then show that the jet's optically thin synchrotron emission accounts for Cygnus X-1's emission beyond 400 keV, although it cannot alone explain its 3-200 keV continuum. A compact jet was also present during the second observation, but we do not detect the break, since it has likely shifted to higher frequencies. In contrast, the compact jet was absent during the last observation, and we show that the 5-30 mu m mid-infrared continuum of Cygnus X-1 stems from the blue supergiant companion star HD 226868. Indeed, the emission can then be understood as the combination of the photospheric Rayleigh-Jeans tail and the bremsstrahlung from the expanding stellar wind. Moreover, the stellar wind is found to be clumpy, with a filling factor f(infinity) approximate to 0.09-0.10. Its bremsstrahlung emission is likely anti-correlated to the soft X-ray emission, suggesting an anti-correlation between the mass-loss and mass-accretion rates. Nevertheless, we do not detect any mid-infrared spectroscopic evidence of interaction between the jets and Cygnus X-1's environment and/or the companion star's stellar wind.
Keywords: binaries: close; dust; extinction; infrared: stars; stars: individual (Cygnus X-1); X-rays: binaries

Chandra X-ray spectroscopy of focused wind in the Cygnus X-1 system. II. The non-dip spectrum in the low/hard state - modulations with orbital phase - Miskovicova, Ivica; Hell, Natalie; Hanke, Manfred; Nowak, Michael A.; Pottschmidt, Katja; Schulz, Norbert S.; Grinberg, Victoria; Duro, Refiz; Madej, Oliwia K.; Lohfink, Anne M.; Rodriguez, Jerome; Bel, Marion Cadolle; et al. (Astronomy & Astrophysics, 2016)
Accretion onto the black hole in the system HDE 226868/Cygnus X-1 is powered by the strong line-driven stellar wind of the O-type donor star. We study the X-ray properties of the stellar wind in the hard state of Cyg X-1, as determined using data from the Chandra High Energy Transmission Gratings. Large density and temperature inhomogeneities are present in the wind, with a fraction of the wind consisting of clumps of matter with higher density and lower temperature embedded in a photoionized gas. Absorption dips observed in the light curve are believed to be caused by these clumps. This work concentrates on the non-dip spectra as a function of orbital phase. The spectra show lines of H-like and He-like ions of S, Si, Na, Mg, Al, and highly ionized Fe (Fe xvii-Fe xxiv). We measure velocity shifts, column densities, and thermal broadening of the line series. The excellent quality of these five observations allows us to investigate the orbital phase-dependence of these parameters. We show that the absorber is located close to the black hole. Doppler shifted lines point at a complex wind structure in this region, while emission lines seen in some observations are from a denser medium than the absorber. The observed line profiles are phase-dependent. Their shapes vary from pure, symmetric absorption at the superior conjunction to P Cygni profiles at the inferior conjunction of the black hole.
Keywords: Accretion; accretion disks; Stars: individual: Cyg X-1; Stars: individual: HDE 226868; Stars: winds; outflows; X-rays: binaries

GRO J1008-57: an (almost) predictable transient X-ray binary - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, F.; Pottschmidt, K.; Rothschild, R. E.; Caballero, I.; Grinberg, Victoria; Schoenherr, G.; Shrader, C.; Klochkov, D.; Staubert, R.; et al. (Astronomy & Astrophysics, 2013)
A study of archival RXTE, Swift, and Suzaku pointed observations of the transient high-mass X-ray binary GRO J1008-57 is presented. A new orbital ephemeris based on pulse arrival-timing shows the times of maximum luminosities during outbursts of GRO J1008-57 to be close to periastron at orbital phase -0.03. This makes the source one of a few for which outburst dates can be predicted with very high precision. Spectra of the source in 2005, 2007, and 2011 can be well described by a simple power law with high-energy cutoff and an additional black body at lower energies. The photon index of the power law and the black-body flux only depend on the 15-50 keV source flux. No apparent hysteresis effects are seen. These correlations allow us to predict the evolution of the pulsar's X-ray spectral shape over all outbursts as a function of just one parameter, the source's flux. If modified by an additional soft component, this prediction even holds during GRO J1008-57's 2012 type II outburst.
Keywords: X-rays: binaries; pulsars: individual: GRO J1008-57; accretion; accretion disks; ephemerides

Long term variability of Cygnus X-1 VI. Energy-resolved X-ray variability 1999-2011 - Grinberg, Victoria; Pottschmidt, K.; Boeck, M.; Schmid, Christian; Nowak, M. A.; Uttley, P.; Tomsick, J. A.; Rodriguez, Jerome; Hell, Natalie; Markowitz, Alex; Bodaghee, A.; Bel, M. Cadolle; et al. (Astronomy & Astrophysics, 2014)
We present the most extensive analysis of Fourier-based X-ray timing properties of the black hole binary Cygnus X-1 to date, based on 12 years of bi-weekly monitoring with RXTE from 1999 to 2011. Our aim is a comprehensive study of timing behavior across all spectral states, including the elusive transitions and extreme hard and soft states. We discuss the dependence of the timing properties on spectral shape and photon energy, and study correlations between Fourier-frequency dependent coherence and time lags with features in the power spectra. Our main results are: (a) The fractional rms in the 0.125-256 Hz range in different spectral states shows complex behavior that depends on the energy range considered. It reaches its maximum not in the hard state, but in the soft state in the Comptonized tail above 10 keV. (b) The shape of power spectra in hard and intermediate states and the normalization in the soft state are strongly energy dependent in the 2.1-15 keV range. This emphasizes the need for an energy-dependent treatment of power spectra and a careful consideration of energy- and mass-scaling when comparing the variability of different source types, e.g., black hole binaries and AGN. PSDs during extremely hard and extremely soft states can be easily confused for energies above similar to 5 keV in the 0.125-256 Hz range. (c) The coherence between energy bands drops during transitions from the intermediate into the soft state but recovers in the soft state. (d) The time lag spectra in soft and intermediate states show distinct features at frequencies related to the frequencies of the main variability components seen in the power spectra and show the same shift to higher frequencies as the source softens. Our results constitute a template for other sources and for physical models for the origin of the X-ray variability. In particular, we discuss how the timing properties of Cyg X-1 can be used to assess the evolution of variability with spectral shape in other black hole binaries. Our results suggest that none of the available theoretical models can explain the full complexity of X-ray timing behavior of Cyg X-1, although several ansatzes with different physical assumptions are promising.
Keywords: X-rays: binaries; stars: individual: Cygnus X-1; binaries: close

Long term variability of Cygnus X-1 V. State definitions with all sky monitors - Grinberg, Victoria; Hell, Natalie; Pottschmidt, K.; Boeck, M.; Nowak, M. A.; Rodriguez, Jerome; Bodaghee, A.; Bel, M. Cadolle; Case, G. L.; Hanke, Manfred; Kühnel, Matthias; Markoff, S. B.; et al. (Astronomy & Astrophysics, 2013)
We present a scheme for determining the spectral state of the canonical black hole Cyg X-1 using data from previous and current X-ray all sky monitors (RXTE-ASM, Swift-BAT, MAXI, and Fermi-GBM). Determinations of the hard/intermediate and soft state agree to better than 10% between different monitors, facilitating the determination of the state and its context for any observation of the source, potentially over the lifetimes of different individual monitors. A separation of the hard and the intermediate states, which strongly differ in their spectral shape and short-term timing behavior, is only possible when data in the soft X-rays (<5 keV) are available. A statistical analysis of the states confirms the different activity patterns of the source (e.g., month- to year-long hard-state periods or phases during which numerous transitions occur). It also shows that the hard and soft states are stable, with the probability of Cyg X-1 remaining in a given state for at least one week to be larger than 85% in the hard state and larger than 75% in the soft state. Intermediate states are short lived, with a 50% probability that the source leaves the intermediate state within three days. Reliable detection of these potentially short-lived events is only possible with monitor data that have a time resolution better than 1 d.
Keywords: X-rays: binaries; stars: individual: Cygnus X-1; binaries: close

Luminosity dependent accretion state change in GRO J1008-57 - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, Felix; Pottschmidt, Katja; Rothschild, Richard E.; Caballero, Isabel; Grinberg, Victoria; Schoenherr, Gabriele; Shrader, Chris; Klochkov, Dmitry; Staubert, Ruediger; et al. (2014)
In a former publication, we have analyzed the transient neutron star X-ray binary GRO J1008-57 using all available RXTE-, Swift-, and Suzaku-data. As we have found, the source's spectral components, i.e., a power-law with high exponential cutoff and a black-body, are strongly correlated with the hard X-ray flux (15-50 keV). We update the analytical description of these dependence, including a change in the photon index behaviour from a flat to a logarithmic function. The flux, where the change occurs, is consistent with the onset of the black-body emission. Thus, a change of the accretion state always occurs in GRO J1008-57 at a particular flux level.

No anticorrelation between cyclotron line energy and X-ray flux in 4U 0115+634 - Müller, Sebastian; Ferrigno, C.; Kühnel, Matthias; Schoenherr, G.; Becker, P. A.; Wolff, M. T.; Hertel, Dominik; Schwarm, Fritz-Walter; Grinberg, Victoria; Obst, M.; Caballero, I.; Pottschmidt, K.; et al. (Astronomy & Astrophysics, 2013)
We report on an outburst of the high mass X-ray binary 4U 0115+634 with a pulse period of 3.6 s in 2008 March/April as observed with RXTE and INTEGRAL. During the outburst the neutron star's luminosity varied by a factor of 10 in the 3-50 keV band. In agreement with earlier work we find evidence of five cyclotron resonance scattering features at similar to 10.7, 21.8, 35.5, 46.7, and 59.7 keV. Previous work had found an anticorrelation between the fundamental cyclotron line energy and the X-ray flux. We show that this apparent anticorrelation is probably due to the unphysical interplay of parameters of the cyclotron line with the continuum models used previously, e. g., the negative and positive exponent power law (NPEX). For this model, we show that cyclotron line modeling erroneously leads to describing part of the exponential cutoff and the continuum variability, and not the cyclotron lines. When the X-ray continuum is modeled with a simple exponentially cutoff power law modified by a Gaussian emission feature around 10 keV, the correlation between the line energy and the flux vanishes, and the line parameters remain virtually constant over the outburst. We therefore conclude that the previously reported anticorrelation is an artifact of the assumptions adopted in the modeling of the continuum.
Keywords: X-rays: binaries; pulsars: individual 4U 0115+634; magnetic fields

Polarized Gamma-Ray Emission from the Galactic Black Hole Cygnus X-1 - Laurent, P.; Rodriguez, Jerome; Wilms, Jörn; Bel, M. Cadolle; Pottschmidt, K.; Grinberg, Victoria (Science, 2011)
Because of their inherently high flux allowing the detection of clear signals, black hole x-ray binaries are interesting candidates for polarization studies, even if no polarization signals have been observed from them before. Such measurements would provide further detailed insight into these sources' emission mechanisms. We measured the polarization of the gamma-ray emission from the black hole binary system Cygnus X-1 with the International Gamma-Ray Astrophysics Laboratory Imager on Board the Integral Satellite (INTEGRAL/IBIS) telescope. Spectral modeling of the data reveals two emission mechanisms: The 250- to 400-keV ( kilo-electron volt) data are consistent with emission dominated by Compton scattering on thermal electrons and are weakly polarized. The second spectral component seen in the 400-keV to 2-MeV band is by contrast strongly polarized, revealing that the MeV emission is probably related to the jet first detected in the radio band.

SPECTRAL STATE DEPENDENCE OF THE 0.4-2 MEV POLARIZED EMISSION IN CYGNUS X-1 SEEN WITH INTEGRAL/IBIS, AND LINKS WITH THE AMI RADIO DATA - Rodriguez, Jerome; Grinberg, Victoria; Laurent, Philippe; Bel, Marion Cadolle; Pottschmidt, Katja; Pooley, Guy; Bodaghee, Arash; Wilms, Jörn; Gouiffes, Christian (Astrophysical Journal, 2015)
Polarization of the greater than or similar to 400 keV hard tail of the microquasar Cygnus X-1 has been independently reported by INTEGRAL/Imager on Board the INTEGRAL Satellite (IBIS), and INTEGRAL/SPectrometer on INTEGRAL and interpreted as emission from a compact jet. These conclusions were, however, based on the accumulation of all INTEGRAL data regardless of the spectral state. We utilize additional INTEGRAL exposure accumulated until 2012 December, and include the AMI/Ryle (15 GHz) radio data in our study. We separate the observations into hard, soft, and intermediate/transitional states and detect radio emission from a compact jet in hard and intermediate states (IS), but not in the soft. The 10-400 keV INTEGRAL (JEM-X and IBIS) state resolved spectra are well modeled with thermal Comptonization and reflection components. We detect a hard tail in the 0.4-2 MeV range for the hard state only. We extract the state dependent polarigrams of Cyg X-1, which are all compatible with no or an undetectable level of polarization except in the 400-2000 keV range in the hard state where the polarization fraction is 75% +/- 32% and the polarization angle 40.degrees 0 +/- 14.degrees 3. An upper limit on the 0.4-2 MeV soft state polarization fraction is 70%. Due to the short exposure, we obtain no meaningful constraint for the IS. The likely detection of a >400 keV polarized tail in the hard state, together with the simultaneous presence of a radio jet, reinforce the notion of a compact jet origin of the >400 keV emission.
Keywords: accretion; accretion disks; black hole physics; stars: individual (Cyg X-1); X-rays: stars

Spectro-timing analysis of Cygnus X-1 during a fast state transition - Böck, Moritz; Grinberg, Victoria; Pottschmidt, K.; Hanke, Manfred; Nowak, M. A.; Markoff, S. B.; Uttley, P.; Rodriguez, Jerome; Pooley, G. G.; Suchy, S.; Rothschild, R. E.; Wilms, Jörn (Astronomy & Astrophysics, 2011)
We present the analysis of two long, quasi-uninterrupted RXTE observations of Cygnus X-1 that span several days within a 10 d interval. The spectral characteristics during this observation cover the region where previous observations have shown the source to be most dynamic. Despite that the source behavior on time scales of hours and days is remarkably similar to that on year time scales. This includes a variety of spectral/temporal correlations that previously had only been observed over CygX-1's long-term evolution. Furthermore, we observe a full transition from a hard to a soft spectral state that occurs within less than 2.5 h - shorter than previously reported for any other similar CygX-1 transition. We describe the spectra with a phenomenological model dominated by a broken power law, and we fit the X-ray variability power spectra with a combination of a cutoff power law and Lorentzian components. The spectral and timing properties are correlated: the power spectrum Lorentzian components have an energy-dependent amplitude, and their peak frequencies increase with photon spectral index. Averaged over 3.2-10 Hz, the time lag between the variability in the 4.5-5.7 keV and 9.5-15 keV bands increases with decreasing hardness when the variability is dominated by the Lorentzian components during the hard state. The lag is small when there is a large power law noise contribution, shortly after the transition to the soft state. Interestingly, the soft state not only shows the shortest lags, but also the longest lags when the spectrum is at its softest and faintest. We discuss our results in terms of emission models for black hole binaries.
Keywords: X-rays: binaries; X-rays: individuals: CygX-1

SUZAKU OBSERVATIONS OF THE HMXB 1A 1118-61 - Suchy, Slawomir; Pottschmidt, Katja; Rothschild, Richard E.; Wilms, Jörn; Fürst, Felix; Barragan, Laura; Caballero, Isabel; Grinberg, Victoria; Kreykenbohm, Ingo; Doroshenko, Victor; Santangelo, Andrea; Staubert, Ruediger; et al. (Astrophysical Journal, 2011)
We present broadband analysis of the Be/X-ray transient 1A 1118-61 by Suzaku at the peak of its third observed outburst in 2009 January and two weeks later when the source flux had decayed by an order of magnitude. The continuum was modeled with a cutoffpl model as well as a compTT model, with both cases requiring an additional blackbody component at lower energies. We confirm the detection of a cyclotron line at similar to 55 keV and discuss the possibility of a first harmonic at similar to 110 keV. Pulse profile comparisons show a change in the profile structure at lower energies, an indication for possible changes in the accretion geometry. Phase-resolved spectroscopy in the outburst data shows a change in the continuum throughout the pulse period. The decrease in the cyclotron resonance scattering feature centroid energy also indicates that the viewing angle on the accretion column is changing throughout the pulse period.
Keywords: pulsars: individual (1A 1118-61); stars: magnetic field; X-rays: binaries; X-rays: stars

THE 5 hr PULSE PERIOD AND BROADBAND SPECTRUM OF THE SYMBIOTIC X-RAY BINARY 3A 1954+319 - Marcu, Diana M.; Fürst, Felix; Pottschmidt, Katja; Grinberg, Victoria; Müller, Sebastian; Wilms, Jörn; Postnov, Konstantin A.; Corbet, Robin H. D.; Markwardt, Craig B.; Cadolle Bel, Marion (Astrophysical Journal Letters, 2011)
We present an analysis of the highly variable accreting X-ray pulsar 3A 1954 + 319 using 2005-2009 monitoring data obtained with INTEGRAL and Swift. This considerably extends the pulse period history and covers flaring episodes in 2005 and 2008. In 2006 the source was identified as one of only a few known symbiotic X-ray binaries (SyXBs), i.e., systems composed of a neutron star accreting from the inhomogeneous medium around an M-giant star. The extremely long pulse period of similar to 5.3 hr is directly visible in the 2008 INTEGRAL-ISGRI outburst light curve. The pulse profile is double peaked and generally not significantly energy dependent although there is an indication of possible softening during the main pulse. During the outburst a strong spin-up of -1.8 x 10(-4) hr hr(-1) occurred. Between 2005 and 2008 a long-term spin-down trend of 2.1 x 10(-5) hr hr(-1) was observed for the first time for this source. The 3-80 keV pulse peak spectrum of 3A 1954 + 319 during the 2008 flare could be well described by a thermal Comptonization model. We interpret the results within the framework of a recently developed quasi-spherical accretion model for SyXBs.
Keywords: binaries: symbiotic; stars: individual (3A 1954+319); stars: neutron; X-rays: binaries

X-RAY AND NEAR-INFRARED OBSERVATIONS OF THE OBSCURED ACCRETING PULSAR IGR J18179-1621 - Nowak, M. A.; Paizis, Adamantia; Rodriguez, Jerome; Chaty, Sylvain; Del Santo, Melania; Grinberg, Victoria; Wilms, Jörn; Ubertini, P.; Chini, R. (Astrophysical Journal, 2012)
IGR J18179-1621 is an obscured accreting X-ray pulsar discovered by INTEGRAL on 2012 February 29. We report on our 20 ks Chandra-High Energy Transmission Gratings Spectrometer observation of the source performed on 2012 March 17, on two short contemporaneous Swift observations, and on our two near-infrared (K-s, H-n, and J(n)) observations performed on 2012 March 13 and 26. We determine the most accurate X-ray position of IGR J18179-1621, alpha(J2000) = 18(h)17(m)52.(s)18, delta(J2000) = -16 degrees 21'31.'' 68 (90% uncertainty of 0.'' 6). A strong periodic variability at 11.82 s is clearly detected in the Chandra data, confirming the pulsating nature of the source, with the light-curve softening at the pulse peak. The quasi-simultaneous Chandra-Swift spectra of IGR J18179-1621 can be well fit by a heavily absorbed hard power law (N-H = 2.2 +/- 0.3 x 10(23) cm(-2) and photon index Gamma = 0.4 +/- 0.1) with an average absorbed 2-8 keV flux of 1.4x10(-11) erg cm(-2) s(-1). At the Chandra-based position, a source is detected in our near-infrared (NIR) maps with K-s = 13.14 +/- 0.04 mag, H-n = 16 +/- 0.1 mag, and no J(n)-band counterpart down to similar to 18 mag. The NIR source, compatible with 2MASS J18175218-1621316, shows no variability between 2012 March 13 and 26. Searches of the UKIDSS database show similar NIR flux levels at epochs six months prior to and after a 2007 February 11 archival Chandra observation where the source's X-ray flux was at least 87 times fainter. In many ways IGR J18179-1621 is unusual: its combination of a several week long outburst (without evidence of repeated outbursts in the historical record), high absorption column (a large fraction of which is likely local to the system), and 11.82 s period does not fit neatly into existing X-ray binary categories.
Keywords: accretion; accretion disks; binaries: close; stars: individual; X-rays: binaries